Economies of Scale and Rural Schools - Robert J. Tholkes; Charles H. Sederberg (Journal of Research in Rural Education, 1990)
The wave or reorganization that changed state systems of common schools from elementary to K-12 organizations during the Twentieth Century is about completed. It was driven by industrialization, mechanization of agriculture, advances in transportation and communications, and depletion of natural resources that changed economic and demographic characteristics of rural areas and resulted in higher educational expectations. Economies of scale arguments were often used and misused to support rural school district consolidation. Additional forces are now affecting rural communities and could generate pressure for another, but less numerically dramatic, wave of reorganization. International markets, decentralized manufacturing, and large scale corporate farming are examples of current trends that are changing rural communities and contributing to increased educational expectations. A second wave of reorganization would again give rise to arguments based on economies of scale. Educational leaders should understand economies of scale, their application to public elementary-secondary education and particular implications for rural schools. Selected references and an overview of the literature from a rural education perspective are presented